Fiqih of Indonesian Tourism (FIT) as A Shari'a Tourism Policy System - Fikri, Muhammad (Universitas Islam Indonesia, 2022)
Shari'a tourism is a trend in Indonesia and the international world because currently Muslim and non-Muslim countries are competing to offer the concept of shari'a tourism. The shari'a tourism discourse still attracts controversy amid society in terms of its legal aspects, concept, and application. The term shari'a tourism is also still being debated because people cannot distinguish between conventional tourism and shari'a tourism and there are differences in narratives such as halal tourism and religious tourism. In addition, the development of shari'a tourism policies in Indonesia also has governance problems. This happens because there is no strong ontological, epistemological, and axiological foundation based on Pancasila values, culture, and local wisdom. The problem that will be answered in this article is how is the Fiqh of Indonesian Tourism (FIT) used as a policy system and strategy for developing shari’a tourism. This research is a literature review using a qualitative method that is descriptive-analytic, through Habermas' critical theory approach. This critical theory paradigm is used as a way of looking at and critiquing previous thoughts such as conventional tourism and shari'a tourism. The findings of this study are the Fiqh of Indonesian Tourism (FIT) which is constructed based on Pancasila values and has an ontological, epistemological, and axiological bases, as well as the results of ijtihad through the maslahah mursalah approach as the basis for legal istinbath, 'urf as a study of law and Islamic legal (fiqhiyyah) rules as a reinforcement of the law. The Fiqh of Indonesian Tourism (FIT) is offered as a consideration in the formulation of government policies and praxis for tourist actors without having to be contaminated by non-Muslim tourists, but Muslim and non-Muslim tourists remain in harmony in carrying out tourism activities and maintaining the existence of local culture and wisdom based on Pancasila values. The Fiqh of Indonesian Tourism (FIT) is also a way of traveling without having to be trapped by the symbol of shari'a tourism, in which tourists, both Muslim and non-Muslim, can still enjoy travel and tourism amenities according to their respective beliefs.